Examining the Influence of Transformational Leadership and Green Culture on Pro-Environmental Behaviors: Empirical Evidence From Florida City Governments. (December 2022) - Azhar, Aisha; Yang, Kaifeng
Despite growing interest in greening initiatives, the environmental performance of public organizations largely depends on the voluntary participation of public employees in undertaking pro-environmental behaviors (PEBs). Can organizations encourage better participation? What is the role of leadership and organizational culture in influencing these behaviors? This study investigates the influence of transformational leadership and organizational green culture on employees' PEBs. Data were collected through a survey of public employees in two city governments in Florida. Confirmatory factor analysis followed by the multiple regression analysis were employed to test the proposed model. Findings reveal that organizational factors have the potential to influence the workplace PEBs, but in a complex manner. Certain barriers are found to significantly moderate the effects of organizational factors on employees' PEBs